ANALISIS STRATEGI INTEGRASI, MERGER DAN KONGLOMERASI PADA PERUSAHAAN DI INDONESIA - Muhamad Gani Fansyah; Tria Ma’rifaturrahmah; Naerul Edwin Kiky Aprianto (Musytari : Jurnal Manajemen, Akuntansi, dan Ekonomi, 2024)
This Integration, mergers and conglomeration are important strategies in improving the competitiveness of companies in Indonesia. This research aims to analyze the meaning, purpose, and implementation of these strategies in the context of Indonesian companies. Using a qualitative approach and descriptive analysis, data was collected through a literature study. The results show that integration aims to strengthen market position, while mergers are often done to reduce competition and improve operational efficiency. Concrete examples are the collaboration between Gojek and Tokopedia that formed GoTo, as well as the implementation of an ERP system by PT Dland Bimasakti Property to increase productivity. This research provides in-depth insights into integration, merger and conglomeration strategies, and their impact on firm performance in Indonesia. The findings are expected to serve as a reference for other companies in formulating the right strategy to face the challenges of an increasingly competitive market.